Influence of graphene on self-assembly of polyurethane and evaluation of its biomedical properties - Patel D.K.; Rana D.; Aswal V.K.; Srivastava S.; Roy P.; Maiti P. (My University, 2025)
Novel aliphatic polyurethane (PU) nanohybrids have been prepared using varying amount of graphene by dispersing it in the early stage of polymerization (in situ) and achieved uniform distribution throughout the matrix, required for the improvement of properties. The alteration of self-assembly in presence of graphene have been explored through X-ray diffraction, small angle neutron scattering, atomic force and optical microscopy in the length scale of nanometer, tens of nanometer, hundreds of nanometer and micron range, respectively, indicating the layer by layer self-assembly of polymer and graphene in nanohybrids. The cause of self-assembly has been studied through spectroscopic techniques like FTIR and UV-vis measurements revealing strong interaction between polymer chain (both hard and soft segments) and graphene which is further confirmed from the depression of melting point and decrease in heat of fusion with increasing graphene content in the nanohybrids. The toughness of nanohybrids in solid state improves considerably as compared to pure PU and the mechanical strength in liquid state also dramatically increases with graphene content showing a dip at a particular frequency depending on the strength of self-assembly (greater for higher graphene content nanohybrid) followed by its reformation at higher frequency. Sustained drug release has been achieved in presence of graphene explaining the phenomena from the greater tortuousity in nanohybrids arising from the 2-D graphene and small but uniform cluster size of self-assembly as compared to pure PU. The suitability of the developed nanohybrids has been testified for its use in biomedical arena by checking the complete biocompatibility of the nanohybrids as compared to pure PU using bone marrow derived mesenchymal stem cells. © 2015 Elsevier Ltd. All rights reserved.